McLuhan and Bergman’s film : wild strawberries - Carrillo, Alberto (2016)
Fil: Fernández, Alejandra de las Mercedes. Universidad Nacional del Nordeste. Facultad de Humanidades. Instituto de Filosofía; Argentina.